DataGramaZero Vol. 14, n. 3 (2013) - Costa Junior, Maurício Pereira da (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
DataGramaZero Vol. 14, n. 3 (2013)Link de acesso ao númerohttp://dgz.org.br/jun13/Ind_aut.htm